Towards a role-based metadata scheme for educational digital libraries : a case study in Singapore - Theng, Yin-Leng (2010)
In this paper, we describe the development of an appropriate metadata scheme for GeogDL, a Web-based digital library application containing past-year examination resources for students taking a Singapore national examination in geography. The new metadata scheme was developed from established metadata schemes on education and e-learning. Initial evaluation showed that a role-based approach would be more viable, adapting to the different roles of teachers/educators and librarians contributing geography resources to GeogDL. The paper concludes with concrete implementation of the role-based metadata schema for GeogDL.